文档介绍:(+x)+x=÷2 
2(X+X+)= 
25000+x=6x 
3200=450+5X+X 
X-=6 
12x-8x= 
*2X=15 
= 
x+= 
x-= 
91÷x= 
X+= 
15x=3 
3x-8=16 
7(x-2)=2x+3 
3x+9=27
18(x-2)=270 
12x=300-4x 
7x+= 
3x÷5= 
30÷x+25=85
×8-2x=6 
6x-×3= 
410-3x=170
3(x+)=21 
+8=43 
6x-3x=18 
7(+x)=
+18=3x 
5×3-x÷2=8 
÷x= 
= 
x÷=90 
9x-40=5 
x÷5+9=21 
48-27+5x=31 
+x+21=56 
x+2x+18=78 
(200-x)÷5=30 
(x-140)÷70=4 
20-9x=×
(x+6)=× 
(-)÷x=4 
x+= 
= 
-x=
÷x= 
5x+=
5(x+8)=102 
x+3x+10=70 
3(x+3)=50-x+3 
5x+15=60 
-5x=2 
×7+4x= 
x÷-= 
4x-×6= 
6x+= 
150×2+3x=690 
2x-20=4 
3x+6=18 
2(+x)= 
(x-3)÷2= 
+9x= 
3x=x+100 
x+= 
6x+18=48 
3(x+)= 
12x-9x= 
13(x+5)=169 
2x-97= 
-48= 
42x+25x=134 
(x+)= 
2(x-3)= 
65x+7=42 
9x+4×=91 
x+=134 
+=51 
89x-43x= 
5x-45=100 
-= 
=2x=56 
4x-x= 
-x=28 
X-= 
15 5X-2X=18 
3X+=5
×2= +x 
26×= 2x+10 
×16―16×=4x 
13 -X=
÷X= 
23x=14x+14 
x+14x=65 
3-5x=80 
+6x=54 
-= 
9+4x=40 
2x+8=16 
23x-14x=14 
X+7x=8 
9x-3x=6
6x-8=4 
5x+x=9 
x-8=6x
2x-6=12 
7x+